Where does philosophy take place in translation? Reflections on the relevance of microstructural translation units within philosophical discourse - Heller, Lavinia; Payne (transl.), Charleton (chronotopos – A Journal of Translation History, 2019)
In the course of the cultural and social turn the problem of the translation unit has been widely marginalized by the attention towards other problems. However, the increasing interest of different disciplines in translation processes occurring in the context of academia and philosophy presses translation studies to (re)consider this issue giving rise to the following questions: What are the crucial translation units which trigger the transformation of a thought collective or the transfer of a thought style (Fleck)? What is the relationship between translation processes on the micro-level of the scientific text and the “transfer” of philosophical thought or the transformations within knowledge cultures? In order to understand the actual contribution of translators to the production of science, it is not enough to acknowledge that certain texts have been translated or not, and by whom. To gain insight into the agency of translators in academic discourse, it is indispensable that we look for their actual philosophical or scientific creativity. With this in mind, the article will focus on the most dense part of philosophical works with regard to technical terminology, namely the glossary. There, micro-structural translation units are concentrated and veritably “put on display”. The aim is to show how this site of terminological meticulousness opens up for the translator a sphere of influence and creativity in the sense of knowledge production.